Evaluación del aprovechamiento de Podocnemis unifilis "taricaya", Osteoglossum bicirrhosum "arahuana" y Arapaima gigas "paiche" entre los años 1994 al 2005 en la Reserva Nacional Pacaya Samiria -lineamientos para una propuesta hacia el desarrollo sostenible - Del Águila Chávez, Javier (2012)
The Iargest number of eggs collected from "taricaya" P. unifilis corresponds to the Samiria river basin with approximately 89,934 units of eggs and the most number of eggs uses are reported in the Yanayacu Pucate river basin with approximately 82,050 units; in the Samiria river basin was reported the largest releases of hatching to the natural environment, the correlation between the number of eggs collected and the number of eggs used was higbJy significant only in the Y anayacu Pucate river basin. In the study period to access the formal use "taricaya" was submitted l3 proposals for management plans (8 in the Pacaya basin, 2 in the Yanayacu Pucate basin, 02 documents aquatic turtle management, O 1 in the Pacaya basin and O 1 in the Samiria river). The Paca ya basin reported the most number of alevinos of "arahuana" O. bicirrhosum extracted from the three basins are significant differences; these differences were significant in the Pacaya and Samiria basins., but not between other basins. In Pacaya basin reported the highest participation of fishermen in fishing operation to catch alevinos of "arahuana", just found significant differences in tbe particípation of fishermen in fishing operations to atch alevinos de "arahuana" in the Pacaya and Samiria basins, and not between in the other basins, in the Y anayacu Pucate basin was obtained higher registers of CPUE, the analysis of variance found significant differences between the Samiria and Yanayacu Pucate basins. In the course of 1994 to 2005, was presented to the administration of the Pacaya Samiria National Reserve (PSNR) 28 documents of proposals of the management plans of "arahuana", of which 20 documents correspond to the Pacaya basin and 8 documents correspond to the Yanayacu Pucate basin. The correlation between the use quantity of "paiche" and the fresh weight and the fresh weight and fresh weight dry salty was highly significant, in the counts performed in the PSNR over the years 1994 to 2005, it was reported that in the basins of Pacaya and Yanayacu Pucate predominated the adults specimens to difference of the Samiria basin youth predominated. Between the years' 1994-2005 presented a total of 3 plans of use "paiche". one document to the Pacaya basin and two for the Yanayacu Pucate basin. The use of eggs "taricaya" not represents significant rent for the management groups, however the environmental contribution is invaluable, the marketing of alevinos of "arahuana generated the best economic gains, the marketing of the "paiche" from the management program of the Dorado lake in the Yanayacu Pucate basin did not generate significant gains in the members of UPC Yacu Tayta